Alaska Native Games and How to Play Them - Brown, Tricia; Spiess, Joni (Book collections on Project MUSE., 2020)
"In this book, you'll learn how to play centuries-old games with intriguing names, like the Eskimo Stick Pull, Ear Weight, Musk Ox Wrestling (no, you don't really wrestle the animal!), and Two-Foot High Kick. What do they require of you? Strength, balance, precision, and endurance. Mental focus. The will to challenge yourself and bring out the best in another. Exactly what's needed for survival in a harsh environment"--